Factors affecting landslides occurrence in agro-ecological zones in the Merek catchment, Iran. - Heshmati, Mosayeb; Abdu, Arifin; Jusop, Shamsuddin; Nik Ab. Majid, Nik Muhamad; Ghaituri, M. (Elsevier, 2011)
Part of the mountainous semi-arid areas of Iran is geologically and topographically susceptible to landslides. A study was conducted at the Merek catchment, Iran which is geologically characterized by limestone, sandstone, shale and marls so as to determine the factors responsible for the occurrence of landslides. In this study, geomorphological units within the catchment were mapped by overlapping geological, topographical, land use and erosion data, using satellite image and GIS. Rocks and soils were sampled within each unit to determine their physico-chemical and mineralogical properties. It was found that landslides have affected about 15% of the Merek catchment and that their occurrence were promoted by unstable soils, being eroded at the rate of 18.57 t ha-1 yr-1. These landslides were initiated by crack formation in areas having smectite, a mineral which can swell and contract, depending on the availability of water. Smectite is the dominant mineral in about 80% of the area affected by landslides. Low aggregate stability in the topsoil further promotes the occurrence of landslides. Field verification showed that landslides occur mainly in the forest where the canopy cover is less than 15% with slope of 10-40%. Deforestation, overgrazing and improper tillage practices were found to accelerate landslides in this catchment.